Humanizing Science through STEAM Challenges - Bahng, EunJin; Hauptman, John (Open textbook library., 2021)
In a science methods course during the Covid19 pandemic, 51 future elementary teachers authored children's books and then read them aloud as part of a giving-back, service-learning activity as Open Educational Resources (OER). The 51 children's stories and their accompanying audiobooks aim to integrate STEM and the Arts to humanize science and scientific inquiry with history and philosophy of science in mind.